Promosi Global Film K-pop Demon Hunters Melalui Integrated Marketing Communication Netflix - Anandita, Aulia Putri; Hidayah, Khikmatul; Rasyidah, Resa (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The development of digital technology and the increasing use of Over-the-Top services have driven significant changes in global film consumption. Netflix, as the largest subscription video on demand platform, has capitalized on these changes through a global marketing strategy that enables standardized content distribution and promotion across multiple countries. One such film that has garnered widespread attention is the K-pop film Demon Hunters, which blends Western animation with Korean culture and has set global viewing records. This study aims to analyze Netflix's implementation of Integrated Marketing Communication in the film's global promotion. The study employed a descriptive method with a qualitative approach and utilized secondary data in the form of journal articles, industry reports, media coverage, digital content, and audience responses on social media. The analysis was conducted based on five elements of Integrated Marketing Communication: advertising, sales promotion, personal selling, public relations, and direct and digital marketing. The results show that Netflix's strategy successfully created effective marketing communications, adapting to Korean popular culture, and enabled the K-pop film Demon Hunters to achieve global viewing records.